2020
DOI: 10.31219/osf.io/w8afg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pro-environmental behavior and morality: An economic model with heterogeneous preferences

Abstract: Some individuals voluntarily engage in costly pro-environmental actions although their efforts have limited direct benefits. This paper proposes a novel economic model with heterogeneous agents explaining why. Each agent has a homo moralis type of preference, which combines selfishness and morality. Morality is modeled here as the payoff an agent receives if all other agents act like her. Our model builds on extant literature showing that homo moralis preferences have an evolutionary advantage to better evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recent research has also highlighted the importance of moral considerations in shaping pro-environmental behavior (Eichner & Pethig, 2021;Lee, 2021;Ayoubi & Thurm, 2020). Eichner and Pethig (2021) emphasized the role of "moral consumers" in climate policy, finding that consumers who prioritize moral and ethical concerns in their decision-making process can significantly contribute to the success of environmental policies.…”
Section: Non-market Approachesmentioning
confidence: 99%
“…Recent research has also highlighted the importance of moral considerations in shaping pro-environmental behavior (Eichner & Pethig, 2021;Lee, 2021;Ayoubi & Thurm, 2020). Eichner and Pethig (2021) emphasized the role of "moral consumers" in climate policy, finding that consumers who prioritize moral and ethical concerns in their decision-making process can significantly contribute to the success of environmental policies.…”
Section: Non-market Approachesmentioning
confidence: 99%
“…Recent research has also highlighted the importance of moral considerations in shaping pro-environmental behavior (Eichner & Pethig, 2021;Lee, 2021;Ayoubi & Thurm, 2020). Eichner and Pethig (2021) and Ayoubi and Thurm (2020) emphasized the role of "moral consumers" in climate policy, finding that consumers who prioritize moral and ethical concerns in their decision-making process can significantly contribute to the success of environmental policies.…”
Section: Non-market Approachesmentioning
confidence: 99%
“…Recent research has also highlighted the importance of moral considerations in shaping pro-environmental behavior (Eichner & Pethig, 2021;Lee, 2021;Ayoubi & Thurm, 2020). Eichner and Pethig (2021) and Ayoubi and Thurm (2020) emphasized the role of "moral consumers" in climate policy, finding that consumers who prioritize moral and ethical concerns in their decision-making process can significantly contribute to the success of environmental policies. Lee (2021) developed and validated a scale to measure consumers' moral preferences, distinguishing between Homo moralis and Homo economicus, and demonstrated that individuals with higher moral preferences are more likely to engage in pro-environmental behavior.…”
Section: Non-market Approachesmentioning
confidence: 99%
“…Voluntary contribution to public goods is not limited to knowledge and data sharing. In fact, whether by financing charity actions that provide no direct personal benefit (Andreoni, 1988; Carpenter & Matthews, 2017), or by performing environmentally friendly actions that are time‐ and effort‐consuming (Ayoubi & Thurm, 2020b; Bruvoll et al, 2002; Sundt & Rehdanz, 2015), selfless contributions to public goods are quite common (Bruhin et al, 2019). Whereas classical models with a homo oeconomicus type of preference would imply no contribution to a public good, empirical evidence from field experiments shows that the level of contribution to the public good is consistently higher than 40% with varying conditions (Andreoni, 1995; Burton‐Chellew et al, 2016; Fischbacher et al, 2001; Ockenfels, 1993).…”
Section: Introductionmentioning
confidence: 99%